Microglial Cell Activation Increases Saturated and Decreases Monounsaturated Fatty Acid Content, but Both Lipid Species are Proinflammatory. Issue 4 (29th January 2014) - Button, Emily B.; Mitchell, Andrew S.; Domingos, Marcia M.; Chung, Jessica H.‐J.; Bradley, Ryan M.; Hashemi, Ashkan; Marvyn, Phillip M.; Patterson, Ashley C.; Stark, Ken D.; Quadrilatero, Joe; Duncan, Robin E.
Abstract: Neuroinflammation is a component of age‐related neurodegenerative diseases and cognitive decline. Saturated (SFA) and monounsaturated (MUFA) fatty acids are bioactive molecules that may play different extrinsic and intrinsic roles in neuroinflammation, serving as exogenous ligands for cellular receptors, or endogenous components of cell structural, energetic and signaling pathways. We determined the fatty acyl profile of BV2 microglial cells before and after acute activation with lipopolysaccharide (LPS). We also investigated the effect of SFA and MUFA pretreatment on the production of an invasive, neurotoxic phenotype in BV2 cells. Acute activation of BV2 microglia resulted in an increase in the relative content of SFA (12:0, 16:0, 18:0, 20:0, 22:0, and 24:0 increased significantly), and a relative decrease in the content of MUFA (16:1n7, 18:1n7, 18:1n9, 20:1n9, 24:1n9 decreased significantly). In agreement, the major stearoyl‐CoA desaturase (SCD) isoform in BV2 cells, SCD2, was significantly down‐regulated by LPS. We next treated cells with SFA (16:0 or 18:0) or MUFA (16:1n7 or 18:1n9), and found that levels of secreted IL6 were increased, as was secreted MMP9‐mediated proteolytic activity. To test the functional significance, we treated SH‐SY5Y neuronal cells with conditioned medium from BV2 cells pretreated with fatty acids, and found a small but significant induction of cell death. Our findings suggest differential intrinsic roles for SFA and MUFA in activated microglial cells, but similar extrinsic roles for these fatty acid species in inducing activation. Expansion of SFA is important during microglial cell activation, but either supplemental SFA or MUFA may contribute to chronic low‐grade neuroinflammation.